Analisis Dimensi Berpikir Kritikal dalam Program Membaca Ekstensif - Prancisca, Stella; Fergina, Ana; Rizqi, Muhammad Ainur; Aminullah, Fajar; Ndaumanu, Decky Y.; Ningsih, Endah Setya (Academy of Education Journal, 2024)
This research aims to analyze critical thinking dimensions in an extensive reading program. The research qualitative research approach, with a case study design. The participants consist of students at the university who take part in extensive reading programs. Data were collected through reading reading logs and tests that measured students' critical thinking. The data collected from the critical thinking test was then analyzed statistically, while the log reading data was processed using a qualitative analysis approach. The results showed that there were differences in students' critical thinking test results before and after participating in the extensive reading program. This result was supported by the participants’ reading logs. The extensive reading program implemented by the researchers may not directly create significant changes in terms of average grades, but the results indicate that the program effectively improves students' overall understanding and critical thinking abilities. Therefore, although the results of the significance test are able to provide an idea of whether the changes that occur between the Pre-Test and Post-Test are random or not, the results of the Ho analysis highlight the substantial impact achieved through the treatment that the researcher provided.